Screen-printed back-to-back electroanalytical sensors: heavy metal ion sensing1. Issue 12 (21st June 2015) - Ruas de Souza, Ana P.; Foster, Christopher W.; Kolliopoulos, Athanasios V.; Bertotti, Mauro; Banks, Craig E.
<x xml:space="preserve">Abstract</x> The back-to-back screen-printed electrochemical sensing approach is applied to the quantification of lead(ii) in drinking water which is independently verified with ICP-OES.